ANALISIS HAKIKAT DAN SUMBER PENGETAHUAN DALAM EPISTEMOLOGI FILSAFAT HUKUM ISLAM - Ricke Riyadi Sadikin; Munandi Shaleh; Wilnan Fatahilah (Ar Rasyiid: Journal of Islamic Studies, 2026)
This study examines epistemology in Islamic legal philosophy by focusing on the nature and sources of knowledge as the foundation of legal formulation. The main issue addressed is how legal truth is understood and how legal knowledge is derived within the framework of Islamic law. The objective is to analyze the relationship between revelation, reason, and social reality in constructing a comprehensive structure of legal knowledge. The method employed is qualitative with a normative-philosophical approach through library research on relevant literature. The results indicate that the nature of knowledge in Islamic law reflects a synthesis between objective truth derived from revelation and interpretative understanding shaped by human context. Meanwhile, the sources of legal knowledge extend beyond revelation to include the roles of reason and social experience, which complement each other. In conclusion, the epistemology of Islamic law is integrative and dynamic, as it combines normative, rational, and empirical dimensions in a balanced manner, thereby maintaining its relevance in responding to societal developments.